Cleavage of the NH2-Terminal Octapeptide of Bothrops asper Myotoxic Lysine-49 Phospholipase A2 Reduces Its Membrane-Destabilizing Effect - Díaz Oreiro, Cecilia (1994)
Bothrops asper myotoxin II was cleaved with cyanogen bromide to determine the role of NH2-terminal amino acid residues in its ability to destabilize negatively charged liposomes and to induce myonecrosis. After treatment, cleaved toxin was separated from its NH2-terminal octapeptide by reversed-phase HPLC. Cleaved myotoxin II lost its capability to disrupt negatively charged liposomes, whereas it maintained approximately one-third of its muscle-damaging effect. No gross antigenic changes were detected after cleavage, as judged by immunoreactivity with polyclonal sera and a set of monoclonal antibodies. However, two of the tested MAbs showed a decreased binding to CB-myotoxin II. We conclude that the NH2-terminal octapeptide has an important role in the membrane-destabilizing activity of this toxin. This domain might directly participate in the binding of toxin to membranes, as well as in its pharmacological activities. Alternatively, conformational changes might occur in cleaved protein, altering its cytotoxic effects by indirectly modifying other important domains.